2020
DOI: 10.1103/physrevlett.125.063202
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Electron Transfer in the Dissociative Multiple Ionization of Argon Dimers

Abstract: We report on an experimental and theoretical study of the ionization-fragmentation dynamics of argon dimers in intense few-cycle laser pulses with a tagged carrier-envelope phase. We find that a field-driven electron transfer process from one argon atom across the system boundary to the other argon atom triggers subcycle electron-electron interaction dynamics in the neighboring atom. This attosecond electron-transfer process between distant entities and its implications manifests itself as a distinct phase-shi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 58 publications
(74 reference statements)
2
18
0
Order By: Relevance
“…Furthermore, by applying methods based on angular streaking developed previously [9,13,14] and with the support from semiclassical trajectory simulations we are able to show that the dominant process underlying the rotation is scattering of the second-emitted electron on the neighboring molecular ion as it is driven away by the strong laser field. This finding adds to the emerging evidence for the key importance of laser-subcycle electron scattering dynamics in strong-field driven dimers [29] and clusters [33].…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Furthermore, by applying methods based on angular streaking developed previously [9,13,14] and with the support from semiclassical trajectory simulations we are able to show that the dominant process underlying the rotation is scattering of the second-emitted electron on the neighboring molecular ion as it is driven away by the strong laser field. This finding adds to the emerging evidence for the key importance of laser-subcycle electron scattering dynamics in strong-field driven dimers [29] and clusters [33].…”
Section: Introductionsupporting
confidence: 62%
“…The orientation of the molecules/dimers was calculated from the fragment ions' momentum vectors p 1 = −p 2 . The reason for this selection was motivated by our recent work [29] in which we found that the ionization behavior of a dimer is strongly influenced by laser-driven electron scattering and transfer processes between the two entities of the dimer. To investigate the influence of such electron scattering processes with the double-pulse method, the dimer axis should be roughly aligned along the dominant ionization direction where the field strength is largest, i.e., the major axis of the polarization ellipse.…”
Section: (C)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, using the argon dimer Ar 2 as a model system for two closely-spaced but separate quantum entities, we demonstrated for the first time CEP-control over electron transfer reactions across system boundaries [23]. We showed that an electron emitted from one argon atom and driven to the other atom by the strong laser field, can become transiently captured before it leaves toward the detector.…”
Section: Introductionmentioning
confidence: 99%